PENYULUHAN DAN PELATIHAN HOME INDUSTRY DI DUSUN KRAJAN DESA KEMIRI KECAMATAN PANTI KABUPATEN JEMBER - Elok Rufaiqoh; Sauqi Mustaqim (As-Sidanah, 2020)
Outreach program carried out by a team from the IAI Al-Qodiri KKM was held in early July 01- 01 September 2019. Located in Panti district, Jember regency, this has made a very significant contribution to the community, especially in Kemiri village and received a very good welcome and high enthusiasm. The home industry counseling and training held in the district of Jember is one way to raise the economic level of the community. As with the government's five priority programs for 2019, one of them is to try to alleviate poverty and inequality. In this training, the Al-Qodiri KKM Team utilized young papaya fruit to become papaya sticks, which are natural products of the local community whose utilization is not optimal. It is hoped that the papaya stick home industry can become a home business with small capital and large profits. Apart from that, it also opens job opportunities for local people and improves their skills. Some of the supporting factors for these activities include: the participants of the socialization have a great willingness to take part in counseling and training on the papaya stick home industry, product marketing by entrusting them to the nearest shops or through social media in the form of Facebook and Whatsapp. Some of the obstacles faced during counseling and training for papaya stick home industry are: (1) there are limitations in supporting facilities for conducting counseling and training, including the absence of LCD and projectors. (2) The training activity which was planned to run for 2 days could not be realized due to collisions with the activities of the participants, the majority of whom were farm laborers, where their activities started from morning to evening. So that the socialization team was a bit troublesome to adjust the time accordingly. (3) it is difficult to access the internet to provide training in papaya stick product marketing because of the lack of signal in the area.